Distributed Denial of Service (DDoS) Analysis on Virtual Network and Real Network Traffic - Anton Yudhana; Imam Riadi; Sri Suharti (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Data communication, computers and computer networks increase the needs and facilitation offered by a variety of server services that are owned by individuals and companies. Servers are the core of continuous communication on the internet and the main factor in the life, development and death of individual businesses or companies that rely on the internet. The other side is also developing rapidly targeting server attacks from starting to weaken performance to crippled, the most popular in the hacker world, namely attacks by bombarding servers with many requests from one computer or more, with one machine to thousands of machines. This study implements several DDoS attack techniques targeted at virtual servers and real servers to determine the type of protocol used and its accuracy and reliability. The research method uses the concept of Robert Maribe Branch (2009) or ADDIE which consists of Analysis, Design, Development, Implementation and Evaluation with the results of successful attacks on the HTTP header on the virtual network and on the real network 85.68%, while the TCP has an accuracy value. 87.75% and the real network produces 90.02%. In addition, the attack using the ping of death on the virtual server was successfully carried out and the real server had an accuracy value of 41.45% so that the attack on the TCP protocol was declared very effective in crippling the target PC or server.